Cyclical Behavior of Concrete-Encased Composite Frame Joints with High Strength Concrete - Lei Zeng; Zhenkun Cui; Yunfeng Xiao; Siqian Jin; Yuanyuan Wu (Advances in Materials Science and Engineering)
This paper presents an application of high strength concrete to concrete-encased composite frame building based on an experimental program. The work emphasized joints behavior under reverse cyclic loading caused by earthquakes to provide information for seismic design. To investigate the internal mechanisms and seismic performance, cyclic loading tests were carried out on five half-scale interior joints. Two design variables were addressed in the research: concrete strength and axial column load. Frame joints performance including crack pattern, failure mode, deformation, ductility, strain distribution, and energy dissipation capacity was investigated. It was found that all joint specimens behaved in a manner with joint panel shear failure. Using high strength concrete increased the joint strength and had relatively little effect on the stiffness and ductility. The axial column load helped the joint strength by better mobilizing the outer part of the joint, but it had an obvious influence on the ductility and energy-dissipating capacity, which can be improved by providing enough transverse reinforcement. A typical crack pattern was also provided which can well reflect mechanical character and damage process. This research should contribute to the future engineering applications of high strength concrete to concrete-encased composite structure.